MENGELOLA SAMPAH, MENGELOLA HATI - I Dewa Putu Eskasasnanda (Jurnal Sejarah dan Budaya, 2013)
Abstract. The Garbage problem is one of important issues faced by Indonesian society today. This problem mainly emerges because Indonesian garbage production are excessive if compared with government ability. As a result, environmental degradation arises from garbage pollution. Households produce the most garbage in Indonesia. Therefore provoking people willingness to sort and reduce their waste is considered to be a solution to minimize garbage impact on the environment. Government awareness should declare by making formal regulation to manage it. Nowadays, although official regulations and most of Indonesians aware of garbage risk on the environment, only some people are willing to sort and reduce their garbage. This paper aims to describe the function and motivation underlies domestic garbage management. A practical guide to sort and reduce our domestic garbage also is presented to motivate management of household garbage